Modification of the Main Deck of Pc40 Using the Sandwich Plate System to Support Marine Defense Operations - Veryawan nanda Perkasa; Sovian Aritonang Djamarel; Hermanto Hermanto (Journal Research of Social Science, Economics, and Management, 2022)
Indonesia is the largest archipelagic maritime country in the world, it should strengthen its ability to secure a very wide territorial waters, in order to ensure the security and safety of shipping in Indonesian jurisdictional. PC 40 ship is a reliable TNI-AL patrol ship with relatively small dimensions and will be easy to operate in archipelagic areas. In general, structural construction on conventional PC 40 ships, along with the times, the Sandwich Plate System material has been found to have characteristics that provide advantages in terms of strength and a simpler structure compared to conventional construction. the construction structure uses conventional aluminum using the Sandwich Plate System material with an aluminum-elastomer-aluminum configuration in the flat plate structure on the main deck of the TNI-AL PC 40 Ship. Analysis based on finite element on main deck construction with load loading. From the simulation results, the maximum stress for aluminum material is 17 MPa using stiffeners, while the construction with sandwich plate material system produces a maximum stress of 15 MPa reducing the use of 15 stiffeners, with maximum deformation for conventional aluminum.